Evaluasi Nilai Stabilitas Pada Aspal AC-WC Dengan Metode SNI 06-2489-1991 - Fahrisal Gunawan; Meriana Wahyu Nugroho; Totok Yulianto; Titin Sundari (Jurnal Sipil Terapan, 2023)
Asphalt concrete is a combination of aggregate, asphalt, with or without additives. To obtain high stability in asphalt concrete, it is necessary to have an aggregate that is well graded, dense, and has small voids between aggregate grains. Asphalt concrete performance testing can be done through the Marshall test. The Marshall Test Tool is used to determine the characteristics of a road pavement layer. One of the Marshall test kits that is still widely used in laboratories is the analog Marshall test kit. This study used an experimental method in the laboratory of the Jombang Regency Public Works Office with core test objects (KOR) made of a mixture of wear-resistant steel (AC-WC) with a thickness of 4 cm each. In this test, 4 core specimens were used in accordance with the 2010 General Highways Specifications (revision 3). With the composition of the constituent materials consisting of Aggregate 0-5 mm (42.2%), Aggregate 5 - 10 mm (33%), Aggregate 10 - 15 mm (16.9%), Filler Cement (1.9%), Asphalt Content (6%) those who get the value of 91.3% (stability) is the final residual stability value, before obtaining this value there are several values listed, namely; value 2,292gr/cm3 (Bj Mix), 5.274% (effective asphalt content), 0.772% (absorption of asphalt), 4.71% (VIM), VMA 16.80% (VIM), 71.97% (VFB ), 1178kg (initial marshall stability) , 3.55mm (flow), 332kg/mm (Marshall quetient).